Assessment of knowledge and attitude of healthcare professionals regarding the use of telemedicine: A cross-sectional study from rural areas of Sindh, Pakistan - Grouve Kumar; Harsha Komal Shardha; Waleed Tariq; Mansoor Ahmed Qazi; Kantesh Kumar; Chandni Maheshwari; Atif Hussain; Atif Hussain; Muhammad Junaid Tahir; Jharna Bai; Muhammad Sohaib Asghar (Frontiers Media S.A., 2022)
BackgroundTelemedicine has proved its significance in the healthcare system, especially during the coronavirus disease 2019 (COVID-19) pandemic as it assists in the provision of early and effective healthcare to those in distant areas. This study aimed to assess the knowledge and attitude of healthcare professionals toward the use of telemedicine in the rural areas of Sindh, Pakistan.Materials and methodsThe cross-sectional study was conducted with 212 healthcare professionals including physicians, consultants, surgeons, residents, dentists, and house officers working in public sector hospitals. The face-to-face method was used for data collection. Chi-square test and logistic regression analysis were applied to find the association between different variables and knowledge and practice of telemedicine using SPSS V 24.ResultsThe knowledge of participants regarding the usability of telemedicine and various tools used for the provision of medical services (video consultations, conferencing, use of applications, software, and online groups) was good. A total of 52.2% of participants showed agreement when they were questioned about being aware of online healthcare service provision. In this study, 52.8% of the participants practiced telemedicine by delivering healthcare services through online consultations. The majority of the participants were surgeons (25.9%), residents (23.1%), and physicians (18.9%). The internet (42.4%) and public media (25.9%) were the major sources of information for telemedicine. A total of 70.5% of participants suggested that strategies and efforts should be directed toward the enhanced implementation of telemedicine. Training in telemedicine as a source of information [OR = 13.02 (95% CI = 3.9-43.6), p < 0.001)] and awareness regarding the effect of telemedicine in healthcare quality [OR = 10.25 (95% CI = 2.9-35.4), p < 0.001)] remained the predicting factors for the practice of telemedicine among healthcare workers using multivariate regression analysis.ConclusionTelemedicine has technologically revolutionized the medical sciences worldwide. The awareness level and usage of telemedicine were good among healthcare professionals in rural Sindh. Telemedicine should be utilized to provide quality healthcare in underprivileged areas by investing in infrastructure and education.